Sistem Open Source Dan Pemanfaatan Bagi Perpustakaan - Jendri Jendri; Nasrul Makdis; Rusdi Aras; Tri Yuliani (Jurnal Ilmu Perpustakaan dan Informasi Islam, 2023)
This research is an open source system and utilization for libraries with the aim of providing information and the use of information technology systems, of course also getting great benefits from the application of open source systems in libraries, so that with this presence it will be effective in carrying out systems in libraries. In research using a qualitative approach and descriptive method to provide an explanation and present the research data that has been analyzed. As for the technical data collection in this study is descriptive then perform processing with analytical techniques which will be formulated in the form of words not numbers. The results of this study indicate that Open source is an open source code, where there is freedom in using it, either to study, add, subtract, modify or re-revise. Everything can be done without having to pay royalties to the previous creator, but is free in the sense that he is responsible by not eliminating the copyright of the creator.